Between chains and light: The abolition of slavery in Tunisia and its World Reflections (1846-1897) - Chamtouri, Fatma (The Algerian Historical Journal, 2026)
In the 19th century, Ahmed Bey abolished slavery in Tunisia in 1846, influenced by European abolitionist movements. Despite this progress, the implementation of abolition faces challenges. After 1846, preliminary measures limited the slave trade, but slavery practices persisted. Freed slaves, especially women, remain economically bound to their former masters. The abolition of slavery in Tunisia in the 19th century was a complex and nuanced process. While it marked a major step towards a more just and egalitarian society, it did not succeed in erasing slavery practices and dependencies inherited from the past. The ambiguity between slavery and servitude, resistance to change and the implications of Islamic law have contributed to maintaining some form of dependence among former slaves, highlighting the complexity of abolition and its lasting impact on Tunisian society.